Application of the X-ray densitometry in the evaluation of the quality and mechanical properties of biomass pellets - Tomazello-Filho, Mario (2015)
https://www.scopus.com/inward/record.url?eid=2-s2.0-84922232547&partnerID=40&md5=5d8df1d4b8ac23dc641702d585cfb57d